The Juridical Construction of Passive Subjective Novation Through Paylater Schemes in Marketplace Business Transactions - Firmansyah; Kurnia Ali Syarif; Hadyan Hashfi (International Journal of Education, Vocational and Social Science, 2026)
Increasingly progressive digital technology is driving significant changes in business transaction practices, particularly through marketplace platforms. This has led to new innovations widely used by consumers, such as paylater services, which allow payments to be routed through third parties, such as fintech companies. This scheme raises questions regarding the legal standing of the parties in an agreement. This paper discusses the legal standing of the parties by focusing on the concept of passive subjective novation, namely the replacement of the debtor's position in an agreement, as regulated in the Civil Code (KUHPerdata). The research method used is normative law with a qualitative descriptive analysis approach referring to statutory regulations, conceptual frameworks, and actual practices in Indonesia. The results show that in paylater transactions, passive subjective novation occurs, where the consumer, who was originally indebted to the seller, is replaced by the paylater service party as the new debtor, while the consumer shifts into a new obligation to the paylater service. This practice is in accordance with the principle of freedom of contract and is legally valid according to the Civil Code, POJK and the ITE Law.